Asymmetric hydrogenation in nanoreactors with encapsulated Rh-MonoPhos catalyst. Issue 3 (9th January 2015) - Zhong, Mingmei; Zhang, Xiaoming; Zhao, Yaopeng; Li, Can; Yang, Qihua
Abstract : Encapsulated multicomponent catalyst, Rh-MonoPhos, in nanoreactors showed excellent catalytic activity in the asymmetric hydrogenation reactions. Abstract : The asymmetric multicomponent catalyst, Rh-MonoPhos, was successfully encapsulated in the nanocages of mesoporous silicas with cage-like structure (FDU-12 and C-FDU-12). The resulting solid catalyst exhibits excellent activity (TOF 2052 h −1 ) and enantioselectivity (93% ee) in the asymmetric hydrogenation of olefin derivatives. The solid catalyst with Rh(MonoPhos)2 in nanocages affords considerably higher activity than that with Rh(MonoPhos)1 or Rh(MonoPhos)3 in nanocages. Combined with the ESI-MS results, it could be supposed that RhL2 (nbd) may be active species or the precursors for active species. Moreover, the solid catalyst with C-FDU-12 (inner surface modified by a thin carbon layer) as host material shows considerably higher activity and enantioselectivity than that with pure silica FDU-12 as host material in the asymmetric hydrogenation of different types of olefin derivatives, indicating that the microenvironment modification is one of the key factors for improving the catalytic performance of the solid catalyst. The solid catalysts possess high stability and could be reused for at least 7 times.